A non‐lethal biopsy technique for sampling subcutaneous adipose tissue of small and medium‐sized birds. Issue 2 (22nd March 2016) - Rocha, Afonso D.; Araújo, Pedro M.; Martinho, Filipe R.; Ramos, Jaime A.; Masero, José A.
ABSTRACT: Analysis of fatty acids from adipose tissue can provide important information about the physiological and nutritional condition of birds. However, non‐lethal biopsy procedures and their potential negative effects on small and medium‐sized birds have not been adequately assessed. We developed a biopsy procedure for collecting small amounts of adipose tissue from the furcular area of small and medium‐sized birds (13–62 g) without adverse effects. The biopsy procedure was performed on Dunlins ( Calidris alpina ), a medium‐sized migratory shorebird, and small hybrid songbirds (European Goldfinch [ Carduelis carduelis ] × Atlantic Canary [ Serinus canaria ]). The biopsy involved making a skin incision 2–3 mm long on one side of the furcular region to collect 2–16 mg of adipose tissue. All birds were monitored for 2 weeks after biopsies to examine potential effects of the procedure on body mass, visible fat deposition, time for wound healing, hematocrit levels, total white blood cell counts, and heterophil:lymphocyte ratios. Visible scars were apparent for 10 d for hybrids and 6 d for Dunlins, with no evidence of infection or abnormal scar tissue formation. Body mass of songbirds did not differ before and after the biopsy, but Dunlins increased body mass and visible fat deposition after biopsy. The collection of adipose tissue in the furcular region was performed only for birds with fat scores ≥2, and the tissue collected never represented more than 0.07% of a bird's body mass; we recommend both these values to avoid any possible unknown negative effects. Our non‐lethal biopsy technique is relatively simple to perform, and we recommend it as an alternative to lethal methods for sampling adipose tissue in studies of wild and captive birds.